Assessing green space cooling effects on the tropical urban microclimate / Siti Norafzan Buyadi - Buyadi, Siti Norafzan (Institute of Graduate Studies, UiTM, 2018)
Urban Heat Island (UHI) is a phenomenon where the temperature distribution in the urban areas is significantly warmer than the surrounding suburban areas. One of the main causes of UHI is the replacement of natural surfaces by built surfaces through urbanisation. Trees and vegetation play vital roles to mitigate the UHI effects, especially by regulating high temperature in saturated urban areas and their surroundings. This study evaluated the effects of land use/land cover on the surface temperature of an urban area, especially in a hot and humid tropical climate like Malaysia. The objectives were to determine the surface temperature distribution within the different land covers, to analyse the vegetation growth impact on land surface temperature, to determine the temperature distribution within parks, to quantify the green space cooling effect intensity, and to analyse the surface temperature distribution of different land covers within 24 hours. The study areas were mainly located within the Petaling Districts, Selangor Darul Ehsan. For a more detailed study to quantify the green spaces cooling effects, Shah Alam Lake Garden (Shah Alam), Bandaran Kelana Park (Kelana Jaya) and Subang Ria Recreational Park (Subang Jaya) were selected as the test sites. Land use/land cover, vegetation, and surface temperature distribution maps were derived from Landsat 5 Thematic Mapper (TM) image of 1991, 1999 and 2009. Other satellite data used in this study were Landsat 8 Operational Land Imager (OLI) and Landsat 8 OLI/ Thermal Infrared Sensor (OLI/TIRS) images of 2013 and 2014. Monowindow algorithm was used to generate temperature distribution maps of the study areas…